Digital competence of Higher Education teachers in research work: validation of an explanatory and confirmatory model - Francisco D. Guillén Gámez; Łukasz Tomczyk; Ernesto Colomo-Magaña; Maria Lidia Mascia (Je-LKS: Journal of E-Learning and Knowledge Society, 2024)
This article demonstrates the validity and reliability of an instrument to evaluate the level of digital competence of Higher Education (HE) teachers in the use of digital resources in research work. The initial instrument was made up of a total of 22 items classified into four dimensions: (DIM. 1. Digital skills to search for information, manage it, analyze it and communicate results; DIM. 2. Digital ethics in digital research; DIM. 3. Digital flow in research work; DIM. 4. Anxiety towards the use of ICT resources for research). The instrument was applied to a final sample of 1709 teachers from different higher education institutions in Spain, from an initial sample of 1740. Reliability was measured using Cronbach’s Alpha and composite reliability. To check the validity of the instrument, the validity of understanding and exploration of dimensionality was analyzed using Exploratory Factor Analysis (EFA), and the instrument was adjusted for the different models using Confirmatory Factor Analysis (CFA). IBM SPSS V.24 software was used for the AFE and AMOS V.24 software was used for the AFC. The result of the reliability analyzes were adequate and, in relation to construct validity, the results found a good fit of the model, both in internal validity and factorial invariance. The final version of the instrument consists of 12 items.